Career Adaptability di Kalangan ASN Muda: Kajian atas Evolusi Cita-cita dan Motivasi Pengabdian - Yuniarti, Nita; Suwandana, Endan; Mulyaningsih, Euis (CERED Indonesia, 2025)
This study aims to understand the dynamics of changing career aspirations among young civil servants and the adaptive meanings that accompany them. The research involved 40 newly recruited Civil Servant Candidates (CPNS) from Tangerang Regency, Banten Province, who had been working for five months and were participating in the Basic Training Program (Latsar) in October 2025. Using a descriptive qualitative approach through anonymous open-ended questionnaires, the study found that most respondents experienced shifts in their aspirations from childhood to adulthood. These changes were influenced by various factors, including access to education, family socioeconomic conditions, personal capacity, and the realities of career opportunities. However, such shifts do not indicate inconsistency in life direction but rather reflect career adaptability, i.e. the ability to negotiate between idealism and professional reality. The young civil servants demonstrated reflective capacity in interpreting these transitions, which contributed to the development of public service motivation and a sense of meaningful work. These findings enrich the literature on career psychology and public management by highlighting the importance of reflective and personal dimensions in shaping the professional identity of young bureaucrats and by encouraging a more humanistic, adaptive, and value-driven approach to civil service development